PIUTANG SIMPAN PINJAM SESUAI DENGAN STANDAR OPERASIONAL PROSEDUR PADA KOPERASI WARGA UNIVERSITAS KRISTEN INDONESIA - Sinaga, Kamer Domician; Malau, Melinda; Tobing, Emerald GM (Fakultas Ekonomi Universitas Kristen Indonesia, 2018)
This research was conducted at UKI Welfare Cooperative, this research focuses on the saving and loan receivables in accordance with the standard operating procedure of UKI Cooperative. The formulation of the problem is whether the savings and loan pitang has been run in accordance with the SOP. The purpose of the research is to provide information about SOP of saving and lending receivables. Accounting process or accounting cycle, related documents and troubled receivables settlement. While its benefits to make input that can make Cooperatives more developed. In this study the authors use primary and secondary data, data collection is by taking data from the accounts receivable saving and loan and conduct direct interviews to employees and Board.In this research, in the provision of savings and loans to members is recognized when the money is submitted to members and billed in the next month for recording the types of receivables has not been applied as a whole in accordance with SOP of UKI Cooperative SOP.Keywords: UKI Cooperative SOP